(untitled) (International Journal of Engineering and Computer Science, 2015)
Cloud becomes a necessity in the real IT world because of its appealing features It becomes a important tool to handle big data. but encryption makes it difficult to perform basic functionalities. Search scheme is cloud supports on exact keyword matching techniques. The synonym or semantic of the keyword is not considered. Hence a scheme is proposed which considers the semantics also of the submitted